The Effect of Crumb Rubber Particle Size to the Optimum Binder Content for Open Graded Friction Course - Mohd Rasdan Ibrahim; Herda Yati Katman; Mohamed Rehan Karim; Suhana Koting; Nuha S. Mashaan (The Scientific World Journal)
The main objective of this paper is to investigate the relations of rubber size, rubber content, and binder content in determination of optimum binder content for open graded friction course (OGFC). Mix gradation type B as specified in Specification for Porous Asphalt produced by the Road Engineering Association of Malaysia (REAM) was used in this study. Marshall specimens were prepared with four different sizes of rubber, namely, 20 mesh size [0.841 mm], 40 mesh [0.42 mm], 80 mesh [0.177 mm], and 100 mesh [0.149 mm] with different concentrations of rubberised bitumen (4%, 8%, and 12%) and different percentages of binder content (4%–7%). The appropriate optimum binder content is then selected according to the results of the air voids, binder draindown, and abrasion loss test. Test results found that crumb rubber particle size can affect the optimum binder content for OGFC.